1996
DOI: 10.1099/0022-1317-77-2-327
|View full text |Cite
|
Sign up to set email alerts
|

Identification of the sequences responsible for nuclear targeting of the V protein of human parainfluenza virus type 2

Abstract: In human parainfluenza virus type 2 (hPIV-2)-infected cells, anti-phosphoprotein (P)-specific monoclonal antibody (MAb) densely stained the perinuclear regions of infected cells throughout infection, indicating that the P protein was localized exclusively in the cell cytoplasm. By contrast, antigens recognized by MAbs directed against the P-V-common domain of hPIV-2 were located predominantly in the cytoplasm, but in some hPIV-2-infected cells they were also found in the nuclei, suggesting that a fraction ofhP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
28
0

Year Published

1998
1998
2016
2016

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(28 citation statements)
references
References 29 publications
(43 reference statements)
0
28
0
Order By: Relevance
“…This difference may be due to differences in the P proteins (which are not conserved as to sequence between these two groups of viruses); the Nterminal domain common to P and V proteins has been shown, in SeV (34) and SV5 (54), to interact with free N protein, i.e., protein that has not been incorporated into nucleocapsids, while SV5 V protein has also been shown to bind to nucleo-capsids (50,59). Both immunofluorescence (65) and biochemical (27) studies of MV V protein have shown it to be distributed throughout the cytoplasm, as is that of SeV (14), whereas the V proteins of hPIV2 (66) and SV5 (51,52) contain nuclear localization signals.…”
Section: Rinderpest Virus (Rpv) Belongs To the Morbillivirus Genus Ofmentioning
confidence: 99%
“…This difference may be due to differences in the P proteins (which are not conserved as to sequence between these two groups of viruses); the Nterminal domain common to P and V proteins has been shown, in SeV (34) and SV5 (54), to interact with free N protein, i.e., protein that has not been incorporated into nucleocapsids, while SV5 V protein has also been shown to bind to nucleo-capsids (50,59). Both immunofluorescence (65) and biochemical (27) studies of MV V protein have shown it to be distributed throughout the cytoplasm, as is that of SeV (14), whereas the V proteins of hPIV2 (66) and SV5 (51,52) contain nuclear localization signals.…”
Section: Rinderpest Virus (Rpv) Belongs To the Morbillivirus Genus Ofmentioning
confidence: 99%
“…Recovery of a completely V-minus rPIV2. The rubulavirus V protein is reported to be multifunctional (22,23,36,47,48). To assess the extent to which the various mutations in V affected its global functions, we attempted the recovery of a recombinant hPIV2 which completely lacks expression of V protein, to provide the other point of reference with which the mutant rPIV2s can be compared.…”
Section: Vol 79 2005 V Protein Of Paramyxoviruses 8595mentioning
confidence: 99%
“…Monoclonal antibodies (MAbs) against hPIV2 P/V protein (85A), hPIV2 V protein (53V), and hPIV2 NP protein (20A) were as described previously (26,27). MAb against hPIV2 P/V protein 85A has cross-reactivity with SV41 P/V protein (47). Anti-STAT1 MAb was purchased from BD Transduction Laboratories (Lexington, KY).…”
Section: Cells and Virusesmentioning
confidence: 99%
“…The V proteins of hPIV2, SV5, and SV41 exhibit characteristic nuclear localization patterns, as described previously (38,52). Strikingly, the hPIV4 V protein was detected exclusively in the cytoplasm (Fig.…”
Section: Resultsmentioning
confidence: 63%